KAJIAN YURIDIS TERHADAP PEMBERIAN KREDIT BANK DENGAN PERSONAL GUARANTEE BANK SWASTA DI KOTA MANADO - Sarah D. L. Roeroe, Betsy Kapugu (LEX ADMINISTRATUM, 2017)
Individual award or Personal Guarantee Agreement is an accesoir of the principal agreement, which is a loan agreement. This can be seen in the provisions of Article 1821 of the Indonesian Civil Code which states